Coping with Macroeconomic Imbalances: Bulgaria's Experience during the Global Turmoil - Rumen Dobrinsky (The Vienna Institute for International Economic Studies (wiiw), 2012)
It is textbook knowledge that economic crises are in most cases associated with the accumulation of macroeconomic imbalances. In turn, macroeconomic imbalances emerge as the result of imbalanced growth. In the ideal world of equilibrium, all macroeconomic variables change at the same, equilibrium growth rate. The real world is one of disharmony and disequilibria, when there are significant divergences in the rates of growth of economic variables. When speed differentials are within certain limits, the resulting macroeconomic imbalances are manageable through the instruments of macroeconomic policy and are not a matter of concern. Crises emerge when disequilibria get out of control and the economy is incapable of coping with significant speed differentials among key economic variables. ...
Keywords: 330